Evaluation of single‐cell force spectroscopy and fluorescence microscopy to determine cell interactions with femtosecond‐laser microstructured titanium surfaces12. Issue 4 (10th September 2012) - Aliuos, Pooyan; Fadeeva, Elena; Badar, Muhammad; Winkel, Andreas; Mueller, Peter P.; Warnecke, Athanasia; Chichkov, Boris; Lenarz, Thomas; Reich, Uta; Reuter, Guenter
Abstract: One goal in biomaterials research is to limit the formation of connective tissue around the implant. Antiwetting surfaces are known to reduce ability of cells to adhere. Such surfaces can be achieved by special surface structures (lotus effect). Aim of the study was to investigate the feasibility for creating antiwetting surface structures on titanium and to characterize their effect on initial cell adhesion and proliferation. Titanium microstructures were generated using femtosecond‐ (fs‐) laser pulses. Murine fibroblasts served as a model for connective tissue cells. Quantitative investigation of initial cell adhesion was performed using atomic force microscopy. Fluorescence microscopy was used for the characterization of cell‐adhesion pattern, cell morphology, and proliferation. Water contact angle (WCA) measurements evinced antiwetting properties of laser‐structured surfaces. However, the WCA was decreased in serum‐containing medium. Initial cell adhesion to microstructured titanium was significantly promoted when compared with polished titanium. Microstructures did not influence cell proliferation on titanium surfaces. However, on titanium microstructures, cells showed a flattened morphology, and the cell orientation was biased according to the surface topography. In conclusion, antiwetting properties of surfaces were absent in the presence of serum and did not hinder adhesion and proliferation of NIH 3T3 fibroblasts. © 2012 Wiley Periodicals, Inc. J Biomed Mater Res Part A, 2012.